Interlinking the human rights to water and sanitation with struggles for food and better livelihoods - Mirumachi, Naho; Griswold, Alison; Mehta, Lyla; Varghese, Shiney; Ringler, Claudia (King's College London, 2022)
Safe and secure access to drinking water and sanitation are human rights that are vital to social, economic, and environmental wellbeing. While interpretations of these rights often focus on domestic water access – for example, whether someone has sufficient drinking water – there is increasing recognition that water for health, food security and nutrition, and basic livelihood needs are inextricably linked. A progressive approach to the human rights to water needs to consider interlinked priorities around food and livelihoods.